A non-hydrocephalic goat experimental model to evaluate a ventriculosinus shunt. (October 2018) - Vandersteene, Jelle; Baert, Edward; Schauvliege, Stijn; Vandevelde, Kimberley; Dewaele, Frank; De Somer, Filip; Van Roost, Dirk
The ventriculosinus shunt is a promising treatment for hydrocephalus. Currently, different shunt techniques exist, and it is not clear whether one is preferable. This pilot study reports on a non-hydrocephalic goat model (Saanen breed) that provides opportunities to evaluate and optimize several aspects of the ventriculosinus shunt technique. Analysis of the coagulation properties of 14 goats by a viscoelastic coagulation monitor showed that goats have a hypercoagulable state compared to humans. This property can be partially counteracted by antiplatelet drugs. During implantation of a ventriculosinus shunt, a pulsatile reflux of blood was observed. After implantation, the animals recovered to their preoperative state, and none of them developed a superior sagittal sinus thrombosis. Evaluation of the shunts after 16 days showed an obstructing luminal clot. Several model-related factors may have promoted this obstruction: the absence of hydrocephalus, the hypercoagulability of caprine blood and the smaller dimensions of the caprine superior sagittal sinus. However, the pulsatile reflux of blood, which is caused by the compliance of the shunt system distal to the valve, may have been an important factor as well. In conclusion, the non-hydrocephalic goat model limits animal suffering and simplifies the study protocol. This model allows researchers to evaluate their implantation technique and shunt hardware but not the efficacy of the treatment or shunt survival.